2021
DOI: 10.1097/md.0000000000027679
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Chinese herbal medicine Buyang Huanwu Decoction combined with acupuncture to treat sequela of apoplexy

Abstract: Background:Stroke is a common disease in neurology, patients often have different degrees of sequelae, which affect the patient's quality of life. We conducted a protocol for systematic review and meta-analysis to assess the efficacy of Buyang Huanwu Decoction combined with acupuncture for the treatment of stroke sequelae.Methods:The current protocol is prepared in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses for Protocols statement guideline. Seven electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As a traditional ancient formula in Fushou Jingmen-Phlegm Gate, it is clearly stated in the original text that “specializes in treating snooze and asthma, with very rapid results [ 26 ].” It has the effect of promoting the lung and lowering qi, clearing heat, and resolving phlegm and can be used to treat asthma with phlegm-heat stagnation in the lung and can be used for asthmatic cough with croupy sound in the larynx or with vicious chills and fever, which is a symptom of wind-cold external bundle and phlegm-heat internal accumulation [ 27 ]. All of the self-prepared Ruling the Lung and Fixing Asthma Tang can treat the imbalance of the declination and purification of the lung qi and can also be clinically applied to some respiratory diseases with heat congestion in the lung [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional ancient formula in Fushou Jingmen-Phlegm Gate, it is clearly stated in the original text that “specializes in treating snooze and asthma, with very rapid results [ 26 ].” It has the effect of promoting the lung and lowering qi, clearing heat, and resolving phlegm and can be used to treat asthma with phlegm-heat stagnation in the lung and can be used for asthmatic cough with croupy sound in the larynx or with vicious chills and fever, which is a symptom of wind-cold external bundle and phlegm-heat internal accumulation [ 27 ]. All of the self-prepared Ruling the Lung and Fixing Asthma Tang can treat the imbalance of the declination and purification of the lung qi and can also be clinically applied to some respiratory diseases with heat congestion in the lung [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported using a randomization procedure to address selection bias. However, details were unclear in 4 studies, [18–21] while 6 [22–27] used a random number table and 3 [28–30] utilized computer-generated random numbers. Due to the nature of herbal decoction, participants were aware of their treatment, leading to a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the nature of herbal decoction, participants were aware of their treatment, leading to a high risk of bias. Only 3 [19,28,30] studies reported adequate blinding of outcome assessment. Six studies [19,21,22,26,28,30] provided adequate reporting of missing data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical studies have indicated the potential therapeutic benefits of combining BYHWD with tetrandrine for silicosis treatment. [10,28] However, the precise mechanism and key active components involved in the combined therapy of tetrandrine and BYHWD remain under investigation.…”
Section: Discussionmentioning
confidence: 99%